Anatomy and palynology of Salvia verticillata subsp. verticillata L. (Lamiaceae), a red-listed species in Turkey - Koyuncu, Onur; Erkara, Ismühan Potoglu; Ardiç, Murat (Bangladesh Journal of Botany, 2010)
Salvia verticillata L. subsp. verticillata has four cornered stem with 5-6 layers of collenchyma cells inside the epidermis. The pith is parenchymatous. In the leaf mesophyll, the palisade and spongy parenchyma cells were of similar shape. The leaf was amphistomatious. The plant was amaryllis mesomorphic and anisocytic type of stomata. The pollen grains were suboblate-subprolate and stephanocolpate. Exine was seen to be tectate-granulate.